A notify: A fingerprint biometric-based and attendance web-based management system with SMS notification for industrial sector / Mohd Nizam Osman ... [et al.] - Osman, Mohd Nizam; Sedek, Khairul Anwar; Maghribi, Mushahadah; Mohd Faisal, Nadia Hidayah (UiTM Cawangan Perlis, 2018)
Managing people is a difficult task and maintaining the attendance record is an important factor for most of the organizations. Meanwhile, in the industrial sector, a precise attendance record system of the employees is important for companies, especially for the payroll process. There are various existing technology that has been implemented to help an industrial sector to manage their attendance records. The use of current technology such as fingerprint biometric scanner and mobile devices as a complement to the software development will benefits to the industrial sector in order to enhance their services. This paper described a fingerprint biometric-based and web-based management system integrated with short message service (SMS) notification for attendance records of the employees known ANotify. It was specifically developed for an industrial sector that uses fingerprint as biometric features for employee attendance, is able to store records of employees' attendance in organized, systematic, and the SMS alert notification to the supervisors about the employee attendance reports. This system was developed based on System Development Life Cycle (SDLC) as a methodology. A user acceptance test was conducted with thirty (30) respondents to determine the effectiveness of the system by evaluating the questionnaire which was categorized into three (3) parts included user interface satisfaction, perceived ease of use, and integration of SMS notification. Results of the system evaluation showed that the system has a positive impact and to be well accepted by users, convenient, economic and reliable method of notification for the attendance records.